The Little Engine that Could - Piper, Watty; Hauman, George; Hauman, Doris (New York : Platt & Munk, 1990)
When the other engines refuse, the Little Blue Engine tries to pull a stranded train full of toys and good food over the mountain.
Keywords: Locomotive; Children's book